Sinner [compact disc, unabridged] - Stiefvater, Maggie, 1981- (Scholastic Audiobooks, 2014)
As Grace hides the vast depth of her love for Sam from her parents and Sam struggles to release his werewolf past and claim a human future, a new wolf named Cole wins Isabel's heart but his own past threatens to destroy the whole pack.